Evaluasi Kemampuan Lahan dan Arahan Penggunaan Lahan di DAS Yeh Ho Kabupaten Tabanan - SANTOSA, CALVIN ALDIATMA; SUMARNIASIH, MADE SRI; DIARA, I WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
Evaluation of Land Capability and Direction of Land Use in the  Yeh Ho Watershed Tabanan Regency Yeh Ho watershed is a type of continuous river with the characteristics of being able to flow water throughout the year and in its upstream there are still many seasonal cultivation activities and permanent buildings, this can trigger landslides and erosion due to varying slopes and heights. The purpose of this study was to determine the land capability class, land use directions and appropriate management actions so that the watershed function remains sustainable. The methods used are surveys and field observations, and laboratory analysis to measure the parameters of the physical and chemical properties of the soil. Land capability is determined based on the results of soil analysis in the field and laboratory, and the direction of land use is determined based on rainfall, slope and soil type. The results of the study were in the land capability class IIe, IIIe, IVe-s-g, VIe-g. From the results of direction of land use, that the Yeh Ho watershed can be directed to four types of land use, namely annual cultivation, protected areas, buffer areas, and seasonal cultivation because the score for calculating land use directions is in the range of 60-175. The recommended land use as management actions are annual crop cultivation (units 1, 5, 7, and 8), high density mixed gardens (units 2, 3, 11, and 12), high density mixed forest gardens (units 4, 9, and 10), area annual crop cultivation (units 6 and 13).